Pengaruh media pembelajaran macromedia flash terhadap kemampuan pemahaman konsep matematika - Indah Lestari; Siti Laelatul Khaeriyah (Math Didactic: Jurnal Pendidikan Matematika, 2018)
The purpose of this study was to determine the effect of macromedia flash learning media on the ability of concept understanding in mathematics learning to construct a triangle and quadrilateral in grade VII students of SMP 223 Jakarta. The research method used was an experiment by taking two sample groups, each of which amounted to 30 students who were taught with different media. The experimental group was taught using macromedia flash learning media and the control group was taught using power point learning media. After experimenting with different media in the two sample groups then given a test in the form of a description with the same problem to find out the results of the learning activities. Furthermore, the data obtained were tested for data requirements, namely the normality test using Chi-square test and homogeneity test using Fisher's test, from the test results both data were normal and homogeneous. After that, the data were analyzed by t-test. Based on the testing, it was concluded that there was an influence of macromedia flash learning media on the ability to understand mathematical concepts.